The Effect of Work-Life Balance, Workload, Compensation, and Organizational Culture on Employee Job Satisfaction in the Capital Market Sector – Financial Services Authority - RR Lissa Arumdari; Subarjo Joyosumarto; Enny Haryanti; Antyo Pracoyo (Jurnal Multidisiplin Indonesia, 2026)
This study aims to analyze the influence of work-life balance, workload, compensation, and organizational culture on employee job satisfaction in the Capital Market sector of the Financial Services Authority (OJK). The background of this research is based on the increasing complexity of the world of work in the financial sector, which demands high performance and fluctuations in the level of employee job satisfaction. The study uses a quantitative approach with a causal associative design (ex post facto). Data were collected through a survey using a questionnaire with a Likert scale administered to employees of the OJK Capital Market sector, with a random sampling technique. Data analysis was carried out using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method to test the relationships between variables. The results show that compensation, workload, and organizational culture have a positive and significant effect on employee job satisfaction, with compensation being the most dominant factor. Meanwhile, work-life balance did not show a significant influence on job satisfaction in the context of this study, so it can be concluded that employee job satisfaction is more influenced by organizational structure and material factors than by the management of work-life balance.